The Study of Ability of Local Ninivite Rocks in Purification of Drinking Water - Ali, Muna Faiq (Al-Khwarizmi Engineering Journal, 2010)
This study is conducted to verify the efficienecy of local Ninivite rock when used in the treatment of drinking water in plants operating currently in the country in order to develop the situation of these stations to cope with the increase in population. Also, this will limit the pollutian which are increasing in the country’s rivers. (Euphrates and Tigris). These rivers are the sources to feed all water treatment plants in the country. The idea is the develop or the modify these stations by replacing part of top layer of sand filters used in these stations with Ninivite rock to operate as filters composed of two medium. The efficiency of this rock is compared with other materials used successfully worldwide in this area, such as activated carbon and anther cite. The comparison is made on the basis of percentage of the removal of turbidity levels, and on the possibility using high filtration rates that exceed the rates currently used in the treatment plants inside the country. A pilot plant in the laboratory scale was built to simulate the treatment plants within the country. It contains all the operating units of traditional basins. These basins are coagulation, floculation, sedimentation and filtration tanks. Filtration unit, in the present study, is formed of the four glass columns (filters), which worked in parallel and on same time. The 20 cm of Ninivite rock activated carbon, anthercite is placed in first, second, third column respectively, the layer is placed above 40 cm of sand layer, and consequently it worked a filter with two mediums. The fourth column contained only sand for a depth of 60 cm to work as filter with single medium. The same size grains of material used in the present study (0.82 mm) and uniformity coefficient which is equal to 106.